Tafsir Maqasidi dan Krisis Lingkungan Global: Kajian Ayat-Ayat Ekologi dalam al-Qur’an - Robi' Nur Muhammad, Alfet; Syaifudin (SAMAWAT: JOURNAL OF HADITH AND QURANIC STUDIES, 2025)
This study aims to explore Qur’anic verses related to ecological principles through the approach of tafsir maqāsidī in order to formulate a contextual Qur’anic environmental ethic. Using a qualitative library research method, this study analyzes verses on the environment through thematic identification techniques and categorization based on the maqāṣid al-sharī‘ah such as ḥifẓ al-nafs, ḥifẓ al-bī’ah, and ḥifẓ al-nasl. The focus of the study is directed at the prohibition of environmental destruction (fasād) and its correlation with global ecological crises such as climate change and deforestation. The results indicate that tafsir maqāsidī is capable of providing a relevant and applicable interpretation of ecological verses and supports the integration of Qur’anic values with modern sustainability principles, particularly in the context of Islamic education and pesantren.